2017
DOI: 10.1111/all.13197
|View full text |Cite
|
Sign up to set email alerts
|

Airway basophils are increased and activated in eosinophilic asthma

Abstract: The number of activated basophils was increased in the sputum of patients with eosinophilic asthma and correlated with airway and blood eosinophils. Our observations suggest that sputum basophils may serve as a biomarker to monitor new therapeutic approaches for the treatment of eosinophilic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 46 publications
6
47
0
1
Order By: Relevance
“…Furthermore, basophil infiltration into skin lesions seems to be more common than previously thought, indicating that they may play important roles in a variety of inflammatory skin diseases . Higher number of basophils were detected in inflammatory skin diseases where eosinophils are present, and those observations are consistent with a recent study which demonstrated a significant correlation between airway basophils and eosinophils in asthma patients …”
Section: The Role Of Basophils In Local Acute Allergic Reactionssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, basophil infiltration into skin lesions seems to be more common than previously thought, indicating that they may play important roles in a variety of inflammatory skin diseases . Higher number of basophils were detected in inflammatory skin diseases where eosinophils are present, and those observations are consistent with a recent study which demonstrated a significant correlation between airway basophils and eosinophils in asthma patients …”
Section: The Role Of Basophils In Local Acute Allergic Reactionssupporting
confidence: 90%
“…This suggests that basophils infiltrate lung tissue in asthma patients. Basophils are increased in the sputum not only from allergic but also of non‐allergic asthmatic patients . The highest numbers of basophils were observed in the lungs of patients with eosinophilic asthma, and there is a strong positive correlation between sputum basophil and eosinophil counts .…”
Section: The Role Of Basophils In Asthmamentioning
confidence: 97%
See 1 more Smart Citation
“…Their superior ability to release Th2‐type cytokines in comparison to lung mast cells indicates an important pro‐allergic immunomodulatory function and recent studies suggest that epithelial factors, such as TSLP, crucially amplify basophil trafficking and production of Th2‐type cytokines from these cells . Basophil IL‐13 responses have also been shown to correlate closely with LPR lung eosinophilia and their increased numbers have been considered as a biomarker for eosinophilic asthma …”
Section: Role Of Mast Cells and Basophils In Health And Diseasementioning
confidence: 99%
“…Mepolizumab (anti‐IL‐5) depletes blood and airway eosinophils, and, clinically , allows down‐titration of oral corticosteroid and a reduction in the frequency of eosinophil‐dependent exacerbations . Basophils also express IL‐5Rα, participate in T2‐mediated inflammatory pathways and have been associated with exacerbation frequency . Whilst basophil progenitors are unlikely to depend on IL‐5 for development, blood basophil counts measured in routine clinical laboratories suggest they decrease following mepolizumab treatment …”
mentioning
confidence: 99%